Weeds as Indicators of Soil Conditions in Lawns and Landscapes - Norma Samuel; Chris Marble (EDIS)
The purpose of this publication is to provide examples of weeds commonly found under certain environmental conditions. While weeds can be an indicator of a certain condition, some weed species can thrive in many different environments and are indicated in the following tables with an asterisk. For example, spotted spurge (Euphorbia maculata) can be indicative of a dry site, but it will grow and spread very well in sites that are over-irrigated also. The presence of one or two weed species is not necessarily diagnostic to a specific cultural problem, but heavy infestations or the presence of multiple species that prefer a particular condition could indicate that cultural practices should be altered.